2014
DOI: 10.1088/0954-3899/41/10/105107
|View full text |Cite
|
Sign up to set email alerts
|

Influences of statistics and initial size fluctuation on high-order cumulants of conserved quantities in relativistic heavy ion collisions

Abstract: By the generator of the UrQMD model, event statistics for the products of kurtosis (κ) and variance (σ 2 ) of net-proton and net-charge multiplicity distributions are carefully studied. It is shown that the statistics at RHIC/BES below √ s N N < 19.6GeV are not sufficient for using the method of Centrality Bin Width Correction (CBWC). Corresponding results are systematically underestimated. A way to improve the CBWC method is proposed. It can remove the statistics dependence of the data and reduce the initial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Moreover, it has been shown in Figure 1 in Ref. [23] that the fluctuation of many sub-samples are out of 3σ of expectation. So the deviation of average from its expectation due to insufficient statistics can not be ignored.…”
Section: Number Of Eventsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, it has been shown in Figure 1 in Ref. [23] that the fluctuation of many sub-samples are out of 3σ of expectation. So the deviation of average from its expectation due to insufficient statistics can not be ignored.…”
Section: Number Of Eventsmentioning
confidence: 97%
“…where X th is theoretical expectation and X exp is experimentally measured mean of moments with finite statistics. Consider the statistics at RHIC/BES I and its uncertainty of the measurements, the result is acceptable if d < 5% [23]. The statistics at RHIC/BES II has a few hundred millions, which is 1-2 magnitudes larger than those at RHIC/BES I.…”
Section: Statistics Dependence Of the Means Of Measured Momentsmentioning
confidence: 99%
“…A critical issue is that the statistics in each of N ch are still considerably limited even with 320M MB events. Our previous studies showed that we must check whether the statistics in each of N ch are sufficient to satisfy the Central Limit Theorem (CLT) when applying the CBWC method in cumulants analysis [36][37][38]. It showed that 90M MB events are not sufficient for analysis of netproton C 6 /C 2 at √ s N N = 11.5 GeV in the UrQMD model.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the acceptance cuts as well as efficiency corrections drastically influence the measured cumulants [21,22]. The initial size fluctuation is also one of the important non-critical effects which exists in all experiment event variables [23,24,25]. What we want to emphasize here is that the techniques to reduce those non-critical effects should be studied carefully case by case for different cumulants.…”
Section: Introductionmentioning
confidence: 99%
“…Similar with the previously published study on κσ 2 (C 4 /C 2 ) [25], we randomly divide the total number of events into 450, 225, 90, 45, 30, 15, 9, and 5 sub-samples. Correspondingly, the number of events for each kind of sub-sample are 1M, 2M, 5M, 10M, 15M, 30M, 50M, and 90M, respectively.…”
Section: Introductionmentioning
confidence: 99%